Nickel penetration into stratum corneum in FLG null carriers—A human experimental study. (6th May 2022) - Julander, Anneli; Liljedahl, Emelie Rietz; Korres de Paula, Helena; Assarsson, Eva; Engfeldt, Malin; Littorin, Margareta; Shobana Anto, Christine; Lidén, Carola; Broberg, Karin
Abstract: Background: The filaggrin gene ( FLG ) plays a role in skin diseases, with the skin barrier function being impaired in FLG null carriers. The role of FLG status in relation to nickel penetration into the skin remains unclear. Objectives: To elucidate the association between FLG status and nickel penetration into stratum corneum (SC) in individuals without self‐reported history of nickel allergy. Methods: Forty participants (23 FLG wt and 17 FLG null) were exposed to a nickel solution (80 μg/cm 2 ) which was applied onto 2 × 2 cm on their left forearm. After 4 h, the area was tape‐stripped with 10 consecutive tapes. Nickel in each tape was quantified using inductively coupled plasma mass spectrometry. Results: The average recovered nickel dose was 35%–48%. A tendency towards lower recovery was seen in FLG null carriers compared to FLG wt carriers, and lower recovery in those with history of skin and/or respiratory symptoms compared to those without such history. This was however not statistically significant. Conclusion: FLG null carriers had less nickel recovered by tape strips compared with FLG wt carriers and, compared with individuals without a history of skin and/or respiratory symptoms, indicating higher nickel penetration into SC for FLG null carriers, but further studies are needed. Highlights: The role of FLG mutations in relation to nickel penetration into skin is unclear. Twenty‐three FLG wild‐type and 17 FLG null mutation carriers were exposed to 80 μg Ni 2+ on a 4 cm 2 area on the lower arm for 4 h. Non‐significantly less nickel was recovered from the FLG null compared to the FLG wild‐type carriers, indicating a higher uptake of nickel in FLG null carriers.